Debate el cuento: Los dos sacerdotes - Olivera Ginez, Maximira (2020)
Currently, we clearly observe that societies have many limitations regarding the development of skills in our students. One of which Peruvians have great difficulty is precisely in the competence of the area of Communication called communicates orally in their mother tongue._x000D_ Precisely by or previously limited that in the present learning strategy the debate has been shaped as a main method, not only to improve the verbal, communicative expression, through the story "the two priests"; but also that the students are protagonists of the development of their own learning, thus consolidating the teacher as a guide agent.